Quality of Life in the City of Trikala (Greece): Attitudes and Opinions of Residents on Green Spaces and Cycling Paths - Garyfallos Arabatzis; Chrysovalantis Malesios; Georgios Kolkos; Apostolos Kantartzis; Panagiotis Lemonakis (Land)
Over recent decades, intense urbanization, city expansion, and unregulated construction have led to a scarcity of green spaces and environmental degradation. Green spaces significantly enhance residents’ quality of life by supporting mental and physical health, improving environmental conditions, and benefiting the local microclimate. However, adding green spaces alone is insufficient for modern cities. Increasing population mobility and demand for sustainable transportation modes highlight the role of bicycles and safe bike lane networks in urban development. This study focuses on the perspectives of Trikala’s citizens regarding the contributions of green spaces to their quality of life and cycling habits, and to the effectiveness of current cycling infrastructure. Using a structured questionnaire, data were analyzed with SPSS through descriptive and multivariate analysis. The results demonstrate a strong public acknowledgment of green spaces and bicycles as essential components for sustainable urban planning. Nevertheless, challenges with bike lane safety and network continuity were evident. This study concludes that enhancing both green spaces and cycling infrastructure is crucial for fostering a more environmentally friendly and healthy urban environment. Policy recommendations include improving bike lane safety and expanding green space access, creating a foundation for sustainable, resilient urban living.